Identificación de espacios confinados en ambientes laborales para prevenir riesgos y accidentes de trabajo en la industria “Danec S.A.”, ubicada en el km1 ½ vía Sangolquí – Tambillo, periodo 2013 - Molina Molina, Édgar Rodrigo (2016)
The present study was made in order to prevent occupational risks and accidents within the DANEC S.A. enterprise, located in the Rumiñahui canton, parish Sangolqui; which was taken preventive measures and identify what are the possible risks within each activity performed by workers. Through the multigas Mx6 ibrid instrument of measurement acquired by the enterprise and adequate inspection ofsafety are found different confined spaces, into which are not identified what kind of toxic gases exist,an adequate analysis, evaluation and control allowed to prevent and take necessary measuresfor the control of these risks by working procedures provided for the department of industrial safety, jointly, with all those responsible for each area of the enterprise….